2016
DOI: 10.3389/fphar.2016.00487
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Factors in Patients with Advanced Penile Cancer Receiving Salvage (2nd or Later Line) Systemic Treatment: A Retrospective, Multi-Center Study

Abstract: Introduction and objectives: Metastatic penile squamous cell carcinoma (PSCC) is associated with dismal outcomes with median overall survival (OS) of 6–12 months in the first-line and <6 months in the salvage setting. Given the rarity of this disease, randomized trials are difficult. Prognostic risk models may assist in rational drug development by comparing observed outcomes in nonrandomized phase II studies and retrospective data vs. predicted outcomes based on baseline prognostic factors in the context of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Currently, the role of anti-epidermal growth factor receptor (anti-EGFR) targeted therapy (cetuximab, panitumumab, and dacomitinib) in the treatment of advanced penile cancer is investigational (recommendation, LE: 1b-) as the available literature is still limited (Necchi et al 2018 ; Carthon et al 2014 ; Brown et al 2014 ; Buonerba et al 2016 ). Anti-EGFR is an option in unresectable, relapsed, and/or metastatic cancer as a second-line treatment, associated or not associated with chemotherapy, after TIP/TPF failure (recommendation, LE: 4), showing a trend to a higher response rate compared with other chemotherapy regimens (Buonerba et al 2016 ). …”
Section: Resultsmentioning
confidence: 99%
“…Currently, the role of anti-epidermal growth factor receptor (anti-EGFR) targeted therapy (cetuximab, panitumumab, and dacomitinib) in the treatment of advanced penile cancer is investigational (recommendation, LE: 1b-) as the available literature is still limited (Necchi et al 2018 ; Carthon et al 2014 ; Brown et al 2014 ; Buonerba et al 2016 ). Anti-EGFR is an option in unresectable, relapsed, and/or metastatic cancer as a second-line treatment, associated or not associated with chemotherapy, after TIP/TPF failure (recommendation, LE: 4), showing a trend to a higher response rate compared with other chemotherapy regimens (Buonerba et al 2016 ). …”
Section: Resultsmentioning
confidence: 99%
“…Taxanes have been shown to be efficacious as part of a multidrug regimen in the front-line setting. 11,12 Despite this proven efficacy, a retrospective chart review by Buonerba et al., 19 which included 65 patients across North America, Europe, and Japan, reported that 74% of the patients received taxanes as second-line chemotherapy. This is consistent with the fact taxanes are not universally used in a first-line setting.…”
Section: Discussionmentioning
confidence: 99%
“…Buonerba et al. 19 retrospectively analysed 65 patients who received second-line systemic therapy. The presence of visceral metastases and haemoglobin ≤10 g/dL were associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 28 patients in total demonstrated 50% response rate with a median progression free survival (PFS) of 3 months (1.5–5.78) [ 51 ]. Another review of 65 patients, of which 17 patients were treated with cetuximab-including regimens, showed a trend for improved response (OR = 5.05, p = 0.077) when compared to those who received taxane-based regimens alone [ 52 ]. These results seem to indicate that although EGFR pathway plays an initial role in penile carcinogenesis, those with advanced disease continue to benefit from standard chemotherapy regimens in addition to anti- EGFR therapy.…”
Section: Current Established and Emerging Targets Of Therapymentioning
confidence: 99%